Awareness of skin lightening products and motivators of their use among Makurdi residents attending Dermatology Clinic in North Central Nigeria - De-Kaa, Niongun L. P.; Akwaras, Nndunno A.; Daniel, David A.; Shaahu, Vivian N.; Swende, Laadi T.; Ornguga, Bamidele O.; Ocheifa, Matthew N.; Atabo, Amodu; Fikin, Aminu (International Journal of Research in Medical Sciences, 2026)
Background: Skin lightening remains a common practice despite its documented risk. Most patients are unaware of their harmful effects, and even when they become aware the desire to lighten the skin supersedes. This behavior is driven by perceptions linking lighter skin with beauty, social status, or racial identity. This study assessed awareness and motivators for using skin lightening agents (SLAs) among Makurdi residents working or attending Federal Medical Centre, Benue State, Nigeria. Methods: A cross-sectional study was conducted from June 21 to August 30, 2023, using a pretested self-administered questionnaire and convenience sampling. Participants included patients, relatives, secondary school pupils, and healthcare workers. Data were analyzed using SPSS version 25, with significance set at p<0.05. Results: Of 421 targeted respondents, 399 participated. The mean age was 31.76±11.77 years; 58.9% were female. The prevalence of skin lightening practice was 50.1%. Common SLAs included creams and soaps with hydroquinone and corticosteroids. Self-reported adverse effects included skin irritation and discoloration. Significant associations existed between skin lightening practice and age, gender, education, occupation, hospital staff category, secondary school status, income below ₦50,000, skin color type, and adverse effects. Independent predictors of skin lightening included gender, marital status, occupation, satisfaction with skin color, perception of attractive skin, prior adverse effects, and a history of skin conditions. Conclusions: High awareness of SLAs does not correlate with knowledge of their harmful effects. Continued use is driven by socio-cultural factors. Public health education and stricter regulation are essential to curb this practice.